Systematic Literature Review: Persepsi Guru terhadap Kebijakan Sistem Zonasi dalam Penerimaan Peserta Didik Baru - Hamidatul Khalifah; Nurhattati Nurhattati; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
This study aims to provide a systematic review of teachers' perceptions regarding the implementation of the school zoning system in Indonesia. The zoning system is a policy designed to allocate students to schools based on their geographical location, with the goal of creating educational equity and reducing access gaps. This abstract reviews various findings from studies focusing on teachers' views on this policy. The method used in this research is a systematic literature review, screening articles from relevant journals and publications related to the topic. The results of the analysis reveal that teachers' perceptions of the zoning system are mixed. Some teachers support the policy as a positive step toward educational equity, while others express concerns about inadequate implementation, administrative issues, and its impact on educational quality. Several studies also suggest that the success of the zoning system depends on policy support, teacher training, and adequate infrastructure at the school level. These findings can serve as a reference for policymakers in designing more effective and inclusive educational policies and provide deeper insights into the challenges and opportunities faced by educators in implementing the school zoning system.